Violent intimacy : family harmony, state stability, and intimate partner violence in post-socialist China - Zheng, Tiantian (London [England] : Bloomsbury Academic, 2022)
"Based on ethnographic research with victims of intimate partner violence since 2014, this book brings to the forefront women's experiences of, negotiations about, and contestations against violence and men's narratives about the reasons for their violence. It foregrounds the role of history, structural inequalities, and the cultural system of power hierarchy in situating and constructing intimate partner violence. Centering on men and women's narratives about violence, this book connects intimate partner violence with invisible structural violence -- the historical, cultural, political, economic, and legal context that gives rise to and perpetuates violence against women. Through examining the ways in which women's lives are constrained by various forms of violence, hierarchy, and inequality, this book shows that violence against women is a structural issue that is historically produced and politically and culturally engaged."--
Introduction -- Chapter 1 - A Social and Cultural History of Intimate Partner Violence in China -- Chapter 2 - Popular Perceptions of Intimate Partner Violence in Postsocialst China -- Chapter 3 - Intimate Partner Violence, Women, and Resistance in Postsocialist China -- Chapter 4 - Worthy vs Unworthy Victims of Sexual Violence in Postsocialist China -- Chapter 5 - The Legal System and Intimate Partner Violence -- Chapter 6 - Activism and Intimate Partner Violence.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Intimate partner violence -- China; Family violence -- China; Electronic books